Acute respiratory infection in children from developing nations: a multi-level study (2016)
Background:Worldwide, acute respiratory infections (ARI) are the leading cause of death of children under 5 years of age. Aim:To assess the accomplishment of the Millennium Development Goal on under-5 mortality particularly related to ARI in developing countries, and to explore the associations between country characteristics and ARI in children under 5 taking into account child, mother and household attributes. Methods:The study included a representative sample of 354,633 children under 5 years from 40 developing nations. A multilevel analysis of data from the Demographic and Health Surveys and the World Bank was conducted. Results:The prevalence of ARI was 13%. Country inequalities were associated with the disease – GINI index (95% CI 1.01–1.04). The country’s per capita gross domestic product (GDP) (95% CI 1.00–1.01) and health expenditure (95% CI 1.01–1.01) affected the relationship between immunization and ARI, while inequalities influenced the relationship between household wealth (95% CI 0.99–0.99) and the disease. Other factors positively associated with ARI were male gender, low birthweight, working mothers and a high-risk indoor environment. Factors associated with ARI reduction were older children, immunization, breastfeeding for more than 6 months, older maternal age, maternal education and planned pregnancy. Conclusions:In developing countries, public health campaigns to target ARI should consider the country’s macro characteristics. At country level, inequalities but not health expenditure or GDP were associated with the disease and were independent of child, family and household characteristics. The effect of immunization on reducing ARI is greater in countries with a higher GDP and health expenditure. The effect of household wealth on ARI is less in countries with fewer inequalities. Reduction of inequalities is an important measure to decrease ARI in developing countries. © 2016 Taylor and Francis.